Penetrance estimates over time to first and second primary cancer diagnosis in families with Li-Fraumeni syndrome: a single institution perspective - Shin, Seung Jun (Cancer Res, 2019)
Li-Fraumeni syndrome (LFS) is a rare autosomal dominant disorder associated with TP53 germline mutations and an increased lifetime risk of multiple primary cancers (MPC). Penetrance estimation of time to first and second primary cancer within LFS remains challenging due to limited data and the difficulty of characterizing the effects of a primary cancer on the penetrance of a second primary cancer. Using a recurrent events survival modeling approach that incorporates a family-wise likelihood to efficiently integrate the pedigree structure, we estimated the penetrance for both first and second primary cancer (PC) diagnosis from a pediatric sarcoma cohort at MD Anderson Cancer Center (MDACC, number of families=189; single primary cancer [SPC]=771; MPC=87). Validation of the risk prediction performance was performed using an independent MDACC clinical cohort of TP53 tested individuals (SPC=102; MPC=58). Findings showed that an individual diagnosed at a later age was more likely to be diagnosed with a second PC. Additionally, TP53 mutation carriers had a hazard ratio of 1.65 (95%CI: 1.1, 2.5) for developing a second PC versus SPC. The area under the ROC curve (AUC) for predicting individual outcomes of MPC versus SPC was 0.77. In summary, we provide the first set of penetrance estimates for SPC and MPC for TP53 germline mutation carriers, and demonstrate its accuracy for cancer risk assessment.